Impact of hospitalization for acute coronary events on subsequent mortality in patients with chronic heart failure - Abrahamsson, Putte; Dobson, Joanna; Granger, Christopher B.; McMurray, John J.V.; Michelson, Eric L.; Pfeffer, Marc; Pocock, Stuart; Solomon, Scott D.; Yusuf, Salim; Swedberg, Karl (European heart journal, 2009)
Aims We explored the impact of having a hospital admission for an acute coronary syndrome (ACS) on the subsequent prognosis among patients with chronic heart failure (CHF). Methods and results A total of 7599 patients with CHF, New York Heart Association Classes II–IV, were randomly assigned to candesartan or placebo. We assessed the risk of death after a first ACS using time-updated Cox proportional hazard models adjusted for baseline predictors. During a mean follow-up of 3.3 years, 1174 patients experienced at least one ACS. Myocardial infarction (MI) was the first ACS in 442 subjects and unstable angina (UA) in 732. After these events, 219 (49.5%) and 167 (22.8%) patients died during follow-up. The early risk of death was more pronounced after MI: 30.2% died within 30 days compared with 3.6% after UA. After an ACS event, the risk of death declined steadily over time, although 18 months after an MI the risk was still twice that of patients without an ACS. Conclusion Patients with CHF, who develop an ACS, have markedly increased subsequent mortality, particularly in the early phase after an MI.